Comparative study of hypoglycemic activity of Morus alba with oral glibenclamide in streptozotocin induced diabetic rats - Reddy, Mamatha; Shaik, Altaf Hussain (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Diabetes is a chronic metabolic disorder that continues to present a major worldwide health problem, characterized by absolute or relative deficiencies in insulin secretion and/or insulin action associated with chronic hyperglycaemia and disturbances of carbohydrate, lipid, and protein metabolism. It is fast growing disease, gains the status of a potential epidemic in India with prevalence of more than 62 million diabetic individuals currently diagnosed with the diabetes. Methods: The study was conducted at Department of Pharmacology, Kurnool Medical College, Kurnool for a period of 1 year from January 2017 to December 2018. Animals used were albino rats, of Wistar strain, weighing between 150-200gm of either sex. The animals were divided into six groups as: control group (I); pathogenic control group (II) injected intravenously (i.v.) with single dose of STZ (60mg/kg); Morus alba stem bark extract (group-III; 200mg/kg), and group-IV (400mg/kg); group-V animals treated with glibenclamide (5mg/kg, p.o.) following STZ treatment; group-VI, animals treated with bark extract per se (400 mg/kg). Results: The results of this study showed a significant decrease blood glucose level, glycosylated heamoglobin level, and reduction in glutathione and insulin level after STZ administration. These parameters were significantly (p<0.05) reversed by extracts dose dependently. Conclusions: Thus, authors conclude that M. alba stem bark extracts produced significant antidiabetic and antioxidant effect which might be due to the presence of bioactive components such as phenolic and flavonoid content in the extract. The study warrants the need for further evaluated in certain other models of diabetes.